Behavior of Educational Organizations and Institutions on Islamic Religious Education Curriculum in Public School - Iroh Suhiroh; Cecep Nikmatullah; Wawan Wahyudin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Human existence in this world does not negate the membership of an organization. Organization is inherent in human life, because humans as social beings cannot live alone, but are manifestations of social beings, humans live in groups, in society, as a nation, and as a state. This research is descriptive research with a qualitative approach. In this study, the researcher wanted to dig up information and information related to the behavior of educational organizations and institutions toward the Islamic Religious Education curriculum in basic education. The data obtained are described in the form of a narrative. The results in this study indicate that organizational behavior and educational institutions are essentially related to each other because the organization is a structure that has a common goal as the structure contained in the educational institution environment. Organizational behavior in educational institutions can be related to the study of what is caused by humans in organizations and how that behavior affects educational institutions. Islamic religious education in schools is more oriented to the level of moral action, namely so that students do not only stop at the competent level but have the will and habits in realizing these religious teachings and values in everyday life.